Rational approach towards enhancing solar water splitting: a case study of Au-RGO/N-RGO-TiO2 - Bharad, Pradnya A.; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Nanoscale, 2015)
A rational approach was employed to enhance the solar water splitting (SWS) efficiency by systematically combining various important factors that helps to increase the photocatalytic activity. The rational approach includes four important parameters, namely, charge generation through simulated sunlight absorption, charge separation and diffusion, charge utilization through redox reaction, and the electronic integration of all of the above three factors. The complexity of the TiO2 based catalyst and its SWS activity was increased systematically by adding reduced graphene oxide (RGO) or N-doped RGO and/or nanogold. Au-N-RGO-TiO2 shows the maximum apparent quantum yield (AQY) of 2.46% with a H-2 yield (525 mu mol g(-1) h(-1)) from aqueous methanol, and overall water splitting activity (22 mu mol g(-1) h(-1); AQY = 0.1%) without any sacrificial agent under one sun conditions. This exercise helps to understand the factors which help to enhance the SWS activity. Activity enhancement was observed when there is synergy among the components, especially the simulated sunlight absorption (or one sun conditions), charge separation/conduction and charge utilization. Electronic integration among the components provides the synergy for efficient solar light harvesting. In our opinion, the above synergy helps to increase the overall utilization of charge carriers towards the higher activity.

Recent developments in solar H-2 generation from water splitting - Rajaambal, Sivaraman; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2015)
Hydrogen production from water and sunlight through photocatalysis could become one of the channels, in the not-so-distant future, to meet a part of ever growing energy demands. However, accomplishing solar water splitting through semiconductor particulate photocatalysis seems to be the `Holy Grail' problem of science. In the present mini-review, some of the critical strategies of semiconductor photocatalysis are focused with the aim of enumerating underlying critical factors such as visible light harvesting, charge carrier separation, conduction and their utilization that determine the quantum efficiency. We attempted to bring out the essential requirements expected in a material for facile water splitting by explaining important and new designs contributed in the last decade. The newly emerged designs in semiconductor architecture employing nanoscience towards meeting the critical factors of facile photocatalysis are elucidated. The importance of band gap engineering is emphasized to utilize potential wide band gap semiconductors. Assistance of metal nanostructures and quantum dots to semiconductors attains vital importance as they are exuberant visible light harvesters and charge carrier amplifiers. Benevolent use of quantum dots in solar water splitting and photoelectrochemical water splitting provides scope to revolutionize the quantum efficiency by its multiple exciton generation features. A list of drawbacks and issues that hamper the much needed breakthrough in photocatalysis of water splitting is provided to invite attention to address them and move towards sustainable water splitting.
Keywords: Hydrogen; nanomaterial; Photocatalysis; quantum dot; Semiconductor; visible light; water splitting